ASSESSMENT OF THE THERAPEUTIC EFFECTIVENESS AND ADVERSE EFFECTS OF ORAL ISOTRETINOIN VERSUS TOPICAL RETINOIDS IN THE TREATMENT OF MODERATE TO SEVERE ACNE VULGARIS (The Research of Medical Science Review, 2025)
Background: Acne vulgaris is a common chronic dermatological condition that affects adolescents and adults, often leading to psychological distress and physical scarring. Management typically involves topical or systemic retinoids, but concerns remain regarding their comparative effectiveness and side effect profiles.Objectives: To assess the therapeutic effectiveness and adverse effects of oral isotretinoin versus topical retinoids in the treatment of moderate to severe acne vulgaris.Study Design & Setting: A randomized, comparative clinical trial conducted at the Dermatology Department of DHQ Teaching Hospital Mirpur AJK from November 2024 to April 2025.Methodology: A total of 120 patients aged 15–35 years with moderate to severe acne were randomized into two groups (n = 60 each). Group A received oral isotretinoin (0.5 mg/kg/day) and Group B received topical retinoids (adapalene 0.1% gel or tretinoin 0.05% cream) for 16 weeks. Effectiveness was assessed using percentage reduction in lesion count and change in Global Acne Grading System (GAGS) score. Adverse effects were recorded throughout the study. Data were analyzed using SPSS v25 with p ≤ 0.05 considered significant.Results: Group A showed a significantly greater reduction in lesion count (82.5% ± 8.3%) and lower GAGS scores (5.2 ± 2.1) compared to Group B (61.4% ± 10.7%, GAGS 10.7 ± 3.4) (p < 0.001). Adverse effects like cheilitis and dry skin were more common in Group A, while local irritation was more frequent in Group B.Conclusion: Oral isotretinoin is more effective than topical retinoids in treating moderate to severe acne but is associated with more systemic adverse effects.